Is Axillary Better Than Femoral Artery Cannulation in Repair of Acute Type A Aortic Dissection?. Issue 2 (March 2019) - Ram, Eilon; Krupik, Yoav; Lipey, Alexander; Shinfeld, Ami; Peled, Yael; Kogan, Alexander; Raanani, Ehud; Sternik, Leonid
Abstract : Objective: We compared early and late outcomes of patients who underwent femoral versus axillary artery cannulation for repair of acute type A aortic dissection. Methods: Between 2004 and 2017, we retrospectively evaluated the clinical outcomes of 135 consecutive patients who underwent emergency surgery for acute type A aortic dissection repair. Patients were divided into 2 groups: those who underwent femoral ( n = 84) and those who underwent right axillary ( n = 51) artery cannulation. Mean patient age was 63 ± 13 years and 88 (65%) were male. Results: Overall operative mortality was 12.6% (axillary 15.7%, femoral 10.7%; P = 0.564). Patients who underwent axillary compared to femoral artery cannulation had a statistically nonsignificant higher operative mortality rate among both stable and unstable patients (13% vs. 6.5%, P = 0.405 and 40% vs. 22.7%, P = 0.818, respectively). While there was no difference in major complication rates, such as stroke, low cardiac output, and surgical revision for bleeding/tamponade, there was a higher incidence of renal failure that required dialysis in patients who underwent axillary cannulation (12% vs. 1%, P = 0.022). Multivariate analysis demonstrated that predictors for the composite endpoint of operative mortality or severe organ malperfusion, such as renal failure or cerebrovascular accident, were hemodynamic instability on admission (OR 3.87; 95% CI, 1.23 to 12.63; P = 0.021), lower preoperative creatinine clearance (OR 0.94; 95% CI, 0.90 to 0.97; P < 0.001); and the use of axillary artery cannulation (OR 4.1; 95% CI, 1.43 to 12.78; P = 0.011). Among those discharged from hospital, the 3-year survival rate was 91% in the axillary group and 87% in the femoral group ( P = 0.772). Conclusions: Based on our experience, emergent surgery for both stable and unstable patients with acute type A aortic dissection demonstrated similar survival rates and significantly less renal impairment when using the femoral cannulation approach.